National treasure - Turteltaub, Jon; Kouf, Jim (Walt Disney Home Entertainment distributed by Buena Vista Home Entertainment ; distributed in the Philippines by Viva Videos, 2005)
Since his childhood, Benjamin Franklin Gates has known that he is a descendant of a long line of people whose job it has been to guard a treasure hidden by the Founding Fathers. They hid clues to its whereabouts in the country's currency and on the back of the Declaration of Independence. Now, Ben has learned of a plot to steal the Declaration, and has only one option: he has to steal it himself. Even if he pulls off this monumental task, keeping the treasure safe is still going to be incredibly hard, especially since the FBI now knows of his plans.